2003
DOI: 10.1074/jbc.m206470200
|View full text |Cite
|
Sign up to set email alerts
|

PAC1 Receptor Activation by PACAP-38 Mediates Ca2+ Release from a cAMP-dependent Pool in Human Fetal Adrenal Gland Chromaffin Cells

Abstract: Previous studies have shown that human fetal adrenal gland from 17-to 20-week-old fetuses expressed pituitary adenylate cyclase-activating polypeptide (PACAP) receptors, which were localized on chromaffin cells. Pituitary adenylate cyclase-activating polypeptide is a 38-residue ␣-amidated neuropeptide (PACAP-38) 1 originally isolated from the ovine hypothalamus for its ability to stimulate cAMP formation in rat anterior pituitary cells. Processing of PACAP-38 can generate a 27-amino acid amidated peptide (PACA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 57 publications
3
26
1
Order By: Relevance
“…Previous studies have shown that rat intracardiac neurons express three PAC 1 receptor isoforms (PAC 1 -short, PAC 1 -HOP1, and PAC 1 -HOP2) as well as VPAC 1 and VPAC 2 receptors (37). The predominant PAC 1 receptor, PAC 1 -HOP, has been shown to evoke release of calcium from intracellular stores via both cAMP and IP 3 pathways in various cell types including neuroepithelial cells, chromaffin cells, astrocytes, and cortical neurons (44,53,54). However, our data indicate that stimulation of PAC 1 has no direct effect on [Ca 2ϩ ] i in neonatal rat intracardiac neurons.…”
Section: Discussioncontrasting
confidence: 54%
“…Previous studies have shown that rat intracardiac neurons express three PAC 1 receptor isoforms (PAC 1 -short, PAC 1 -HOP1, and PAC 1 -HOP2) as well as VPAC 1 and VPAC 2 receptors (37). The predominant PAC 1 receptor, PAC 1 -HOP, has been shown to evoke release of calcium from intracellular stores via both cAMP and IP 3 pathways in various cell types including neuroepithelial cells, chromaffin cells, astrocytes, and cortical neurons (44,53,54). However, our data indicate that stimulation of PAC 1 has no direct effect on [Ca 2ϩ ] i in neonatal rat intracardiac neurons.…”
Section: Discussioncontrasting
confidence: 54%
“…It is well established that PACAP increases [Ca 2ϩ ] i by mobilizing intracellular pools or by increasing extracellular calcium influx (Chatterjee et al, 1996;Przywara et al, 1996;Osipenko et al, 2000;Morita et al, 2002;Liu et al, 2003;Payet et al, 2003). Our data favor the notion that in cortical precursors PACAP promotes calcium entry from the extracellular milieu, in agreement with previous reports indicating that PACAPinduced Ca 2ϩ influx requires the activation of cAMP-dependent signaling (Przywara et al, 1996;Osipenko et al, 2000).…”
Section: Dream As a Transcriptional Transactivator Of The Gfap Genesupporting
confidence: 83%
“…Incubation of adrenomedullary cells in calcium-free medium or blockage of voltage-operated calcium channels suppresses the PACAP-evoked stimulation of catecholamine secretion (Isobe et al, 1993;Houchi et al, 1995; PITUITARY ADENYLATE CYCLASE-ACTIVATING POLYPEPTIDE Przywara et al, 1996;O'Farrell and Marley, 1997), indicating that the effect of PACAP on chromaffin cells is mediated through calcium influx. Concurrently, in bovine and human, PACAP increases calcium levels from ryanodine/caffeine-sensitive calcium stores (Houchi et al, 1995;Tanaka et al, 1996Tanaka et al, , 1998Shibuya et al, 1999;Payet et al, 2003). The effect of PACAP on catecholamine release is associated with an increase in the expression of tyrosine hydroxylase, dopamine ␤-hydroxylase, and phenylethanolamine N-methyltransferase (Houchi et al, 1994;Rius et al, 1994;Isobe et al, 1996;Marley et al, 1996;Tönshoff et al, 1997;Hong et al, 1998;Choi et al, 1999;Park et al, 1999).…”
Section: E Effects Of Pituitary Adenylate Cyclase-activating Polypepmentioning
confidence: 99%